INTEGRATION OF TRADITIONAL CULTURE AND MODERN TECHNOLOGY: AN EXPLORATION OF THE OPTIMIZATION OF CULTURAL ELEMENTS AND WATER SELF-PURIFICATION SYSTEMS IN THE TRADITIONAL CHINESE WATERSCAPE DESIGN - Yue Zixuan (Russian Studies in Culture and Society)
Traditional Chinese waterscape design is a profound cultural symbol and a perfect embodiment of the natural landscape. The philosophical ideas, aesthetic concepts and cultural connotations embedded in traditional Chinese culture have played an important role in the design of traditional water features. However, traditional water features have struggled to maintain their lasting beauty due to their impact on the environment and ecology. With the development of modern technology and advances in water management theory and techniques, modern water treatment systems have become an important means of solving water management and ecological and environmental problems. Combining traditional cultural elements with modern water self-purification systems has become an effective way to optimise traditional water features.